2015
DOI: 10.1155/2015/740212
|View full text |Cite
|
Sign up to set email alerts
|

Combination Antiretroviral Therapy for HIV in Rwandan Adults: Clinical Outcomes and Impact on Reproductive Health up to 24 Months

Abstract: Adult women (n = 113) and men (n = 100) initiating combination antiretroviral therapy (cART) and women not yet eligible for cART (n = 199) in Kigali, Rwanda, were followed for 6–24 months between 2007 and 2010. In the cART groups, 21% of patients required a drug change due to side effects and 11% of patients had virological failure (defined as >1,000 HIV RNA copies/mL) after 12 months of cART. About a third of the pregnancies since HIV diagnosis were unintended. The proportion of women in the pre-cART group us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…Two studies found no difference in pregnancy incidence by ART and one found higher pregnancy incidence among women not yet on ART than among those on ART , but these studies did not adjust for sociodemographic or health differences between the groups.…”
Section: Resultsmentioning
confidence: 98%
“…Two studies found no difference in pregnancy incidence by ART and one found higher pregnancy incidence among women not yet on ART than among those on ART , but these studies did not adjust for sociodemographic or health differences between the groups.…”
Section: Resultsmentioning
confidence: 98%
“…Patients with HIV infections are at risk of acute and chronic kidney diseases due to antiretroviral drugs and the balance of electrolytes and fluid can be altered leading to an imbalance of certain electrolytes and patients are at an increased risk of death 6 . This study was conducted to assess the kidney function and explore the association with electrolytes imbalance that can increase the risk of death in HIV patients under ART.…”
Section: Introductionmentioning
confidence: 99%